Easier Set Than Done: Stakeholder Engagement as Public-Private Partnership in Regulatory Policy of South Korea - Jongyearn Lee (KDI Journal of Economic Policy, 2019)
An emphasis on public-private partnership (PPP) in the regulatory policy process can overcome the challenges hindering regulatory effectiveness with the emergence of fast developing technologies and new industries. This study attempts to evaluate quantitatively different aspects of institutional settings of South Korean regulatory policy in terms of stakeholder engagement as PPP, using evidence-based data released by the OECD. From the results of the principal component analysis, South Korea can be evaluated as being at a very good level overall in its institutional establishment. Nevertheless, the fact that the outcome of regulatory reforms in South Korea is still insufficient compared with this well-established system suggests that the country should concentrate on improving system operation. Consequently, this study makes policy suggestions to improve regulatory effectiveness through PPP by supplementing the facets that are well-equipped but not feasible with respect to regulatory policy cycle, regulatory governance, regulatory method, and conflict resolution.
Keywords: K20; L50; H11; H83; D74; 330; Regulatory Policy Process; Public-Private Partnerships; Stakeholder Engagement